Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có : (-123) + 77 + (-257) + 23 - 43
= (-123 + 23) + (77 - 257) - 43
= -100 + 180 - 43
= 80 - 43
= 37
\(\left(-123\right)+77+\left(-257\right)+23-43\)
\(=\left(-123\right)+23+\left(-257\right)+77-43\)
\(=\left(-100\right)+\left(-180\right)-43\)
\(=\left(-280\right)-43=-323\)
a) -329 + ( 27 - 111 ) - ( 127 - 440 )
= -329 + 27 - 111 - 127 + 440
= -329-111 -127 + 27 +440
= -440 - 100 +440
=-100
b) ( 157 - 984 ) - ( 16 - 74 ) - ( 374 - 243 )
= 157 - 984 - 16 +74 - 374 + 243
= 157 + 243 - 984 - 16 -374 + 74
= 400 - 1000 - 300
= 100 - 1000
= -900
a, (-20) + 16 + (-34) + 20 = [(-20) + 20] + [16 + (-34)] = 0 + (-18) = (-18) b, 12 + 3.[39 - (5 - 2)2] = 12 + 3.[39 - 32] = 12 + 3.[39 - 9] = 12 + 3.30 = 12 + 90 = 102
MK lm bài 1:
\(\left(a-b\right)\left(a+b\right)=a^2+ab-ab-b^2=a^2-b^2\)
Bài 1:
\(\left(a-b\right)\left(a+b\right)=a^2+ab-ab-b^2\)
\(=a^2-b^2\)